Switzerland and Sub-Saharan Africa in the Cold War, 1967-1979 : neutrality meets decolonisation - Widmer, Sabina (New perspectives on the Cold War, 2021)
"In Switzerland and Sub-Saharan Africa in the Cold War, 1967-1979, Sabina Widmer analyses Swiss foreign policy in Angola, Mozambique, Ethiopia, and Somalia in the late 1960s and 1970s, at the crossroads of the global East-West confrontation and decolonisation. Focusing on the independence wars in Angola and Mozambique, the Angolan War, and the Ogaden War, as well as regime changes that brought Soviet-allied governments to power, this book sheds new light on Switzerland's role in the Third World during the Cold War. Based on extensive multi-archival research, it exposes the limits of neutrality in North-South relations, reveals the growing marge de manoeuvre of small states during Détente, and highlights the role of non-state actors in the making of foreign policy"--